An oligosaccharyltransferase from Leishmania donovani increases the N-glycan occupancy on plant-produced IgG1 - Beihammer, Gernot; König-Beihammer, Julia; Kogelmann, Benjamin; Ruocco, Valentina; Grünwald-Gruber, Clemens; D’Aoust, Marc-André; Lavoie, Pierre-Olivier; Saxena, Pooja; Gach, Johannes S.; Steinkellner, Herta; Strasser, Richard (Frontiers in Plant Science, 2023)
N-Glycosylation of immunoglobulin G1 (IgG1) at the heavy chain Fc domain (Asn297) plays an important role for antibody structure and effector functions. While numerous recombinant IgG1 antibodies have been successfully expressed in plants, they frequently display a considerable amount (up to 50 %) of unglycosylated Fc domain. To overcome this limitation, we tested a single-subunit oligosaccharyltransferase from the protozoan Leishmania donovani (LdOST) for its ability to improve IgG1 Fc glycosylation. LdOST fused to a fluorescent protein was transiently expressed in Nicotiana benthamiana and confocal microscopy confirmed the subcellular location at the endoplasmic reticulum. Transient co-expression of LdOST with two different IgG1 antibodies resulted in a significant increase (up to 97 %) of Fc glycosylation while leaving the overall N-glycan composition unmodified, as determined by different mass spectrometry approaches. While biochemical and functional features of "glycosylation improved" antibodies remained unchanged, a slight increase in FcγRIIIa binding and thermal stability was observed. Collectively, our results reveal that LdOST expression is suitable to reduce the heterogeneity of plant-produced antibodies and can contribute to improving their stability and effector functions.